Law 30886 and the new regulation of the judicial travel authorization of minors. - Balarezo Reyes, Emilio José (2019)
In order to enable the transfer of minors with their parents and the proper exercise of this practice, Law No. 30886 was introduced, which incorporates article 112 - A into the Code of Children and Adolescents, establishing the limitations and restrictions that will be given to the father who is in an undue situation regarding the proper exercise of parental authority when he has not been disqualifying leaving the Specialized Judge in power to decide whether or not to intervene in the approval of the trips that the child or minor may take, analyzing in this way the power of exercise that he has, without the intervention of the Public Ministry, prioritizing the speed of decision making under factors that guide an adequate decision that is based on the benefit of the minor.